Chlorambucil plus rituximab with or without maintenance rituximab as first‐line treatment for elderly chronic lymphocytic leukemia patients. Issue 5 (18th February 2014) - Foà, Robin; Del, Ilaria; Cuneo, Antonio; Del, Giovanni; Ciolli, Stefania; Di, Francesco; Lauria, Francesco; Cencini, Emanuele; Rigolin, Gian Matteo; Cortelezzi, Agostino; Nobile, Francesco; Callea, Vincenzo; et al.
<x xml:space="preserve">Abstract</x> In a phase II trial, we evaluated chlorambucil and rituximab (CLB‐R) as first‐line induction treatment with or without R as maintenance for elderly chronic lymphocytic leukemia (CLL) patients. Treatment consisted of eight 28‐day cycles of CLB (8 mg/m2/day, days 1–7) and R (day 1 of cycle 3, 375 mg/m2; cycles 4–8, 500 mg/m2). Responders were randomized to 12 8‐week doses of R (375 mg/m2) or observation. As per intention‐to‐treat analysis, 82.4% (95% CI, 74.25–90.46%) of 85 patients achieved an overall response (OR), 16.5% a complete response (CR), 2.4% a CR with incomplete bone marrow recovery. The OR was similar across Binet stages (A 86.4%, B 81.6%, and C 78.6%) and age categories (60–64 years, 92.3%; 65–69, 85.2%; 70–74, 75.0%; ≥75, 81.0%). CLB‐R was well tolerated. After a median follow‐up of 34.2 months, the median progression‐free survival (PFS) was 34.7 months (95% CI, 33.1–39.5). TP53 abnormalities, complex karyotype, and low CD20 gene expression predicted lack of response; SF3B1 mutation and BIRC3 disruption low CR rates. IGHV mutations significantly predicted PFS. R maintenance tended towards a better PFS than observation and was safe and most beneficial for patients in partial response and for unmutated IGHV cases. CLB‐R represents a promising option for elderly CLL patients. Am. J. Hematol. 89:480–486, 2014. © 2014 Wiley Periodicals, Inc.